Coronavirus Disease 2019 (COVID-19)- Associated central retinal vein occlusion: A case report and literature review - Mohammad Hassan Hodroj; Ziad F Bashshur; Charbel Wahab; Kawthar Jarrah; Ali Taher (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2022)
Coronavirus Disease 2019 (COVID-19) is caused by the Severe Acute Respiratory Syndrome Coronavirus 2(SARS-CoV-2) that is associated with several inflammatory and vascular endothelial complications. Ocular vascular occlusive events were reported in COVID-19 patients including both Central Retinal Vein Occlusion (CRVO) and Central Retinal Artery Occlusion (CRAO). We report a case of a 34-years-old patient with right CRVO after 14 days of COVID-19 infection presenting with decreased vision. In addition, we provide a summary of both CRVO and CRAO reported in the literature.